Duplex ultrasound in upper and lower limb deep venous thrombosis - Tsongo V Sosthène; Kahatwa K Serge; Kabuyaya K Medard; Kighoma V Simplice; Musubao K John; Serugendo S Albin (Annals of Circulation - Peertechz Publications, 2020)
Duplex ultrasound involves B-mode and Doppler ultrasound. Duplex ultrasonography is a radiological examination requested by clinicians in patients with symptoms of deep venous thrombosis such as upper or lower limb swelling, pain and tenderness. Deep venous thrombosis is a pathology in which clot formation causes obstruction of blood flow. The lower limbs are more affected by DVT than upper limbs. Several radiological investigations may be helpful to make the diagnosis. Ultrasound remains a non-ionic, non-invasive, cheaper, available and accurate investigation for prompt diagnosis of DVT however Duplex USG must be done by a radiologist or an experimented sonographer. The sonographic findings may be of acute or chronic DVT. In acute DVT, the intra luminal blood clot is hypoechoic or anechoic whereas in chronic DVT, it is hyperechoic with peripheral revascularization on color Doppler imaging. The results of Doppler ultrasound are sent to clinicians for good treatment plan and follow-up. The treatment is urgent in acute DVT to prevent pulmonary embolism, a life-threatening complication with high mortality rate.